2013
DOI: 10.11646/zootaxa.3734.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the knowledge of the genus Dicronychus (Coleoptera: Elateridae) from the Kingdom of Saudi Arabia

Abstract: Examination of specimens of Dicronychus Brullé in the King Saud University Museum of Arthropods, Riyadh, Saudi Arabia revealed the presence of two new species, D. latifae n. sp. and D. bushrae n. sp. In addition, the descriptions of D. talhouki Platia and Schimmel and D. brancuccii Platia and Schimmel are augmented after examination of both type material and recently collected specimens from the Kingdom of Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The flora and fauna of these unique habitats are under constant threat due to increased anthropogenic activities ( Al-Nafie 2007 ; Al-Qarawi 2011 ). However, relatively little is known about their insect fauna (e.g., Al Dhafer and Platia 2013 , Al Dhafer et al 2016 ; Sharaf et al 2013 ; Alqarni et al 2015 ; Abdel-Dayem et al 2015 , 2016 ) that contribute to the faunal biodiversity of KSA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flora and fauna of these unique habitats are under constant threat due to increased anthropogenic activities ( Al-Nafie 2007 ; Al-Qarawi 2011 ). However, relatively little is known about their insect fauna (e.g., Al Dhafer and Platia 2013 , Al Dhafer et al 2016 ; Sharaf et al 2013 ; Alqarni et al 2015 ; Abdel-Dayem et al 2015 , 2016 ) that contribute to the faunal biodiversity of KSA .…”
Section: Introductionmentioning
confidence: 99%
“…( Tag El-Din et al 1994 ; Al-Farraj et al 1997 ; Alfarhan 2001 ; Al-Qarawi 2011 ). Recent studies of the insects occurring in RKNP have revealed several new taxa, Coleoptera : Dicronychus latifahae ( Elateridae ) ( Al Dhafer and Platia 2013 ); Reichardtiolus aldhaferi ( Histeridae ) ( Lackner 2014 ); Boromorphus saudicus ( Tenebrionidae ) ( Schawaller et al 2013 ); and Hymenoptera : Tetramorium saudicum ( Formicidae ) ( Sharaf et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The generic compositions of the tribes and subfamilies treated in this study are as follows: Agrypnini sensu Hayek (1973Hayek ( , 1979 Agrypninae, but excluding Lanelater Arnett, 1952), with genera added by Chassain (1983), Gurjeva (1987) and Arias-Bohart (2014), and changes by Gurjeva (1977), Cate et al (2007), and Girard (2017); Anaissini sensu Golbach (1984), including Alampina of Costa (1975); Euplinthini sensu Costa (1975), with changes by Johnson (2002b) and Arias-Bohart and Elgueta (2012); Drilini sensu Bocak (2011, 2017); Hemirhipini sensu Casari (2008;but excluding Anthracalaus Fairmaire, 1888), with changes by Patwardhan et al (2009), Schimmel and Tarnawski (2012), and Arimoto and Arimoto (2017); Oophorini sensu Johnson (1995Johnson ( , 1997 and Cate et al (2007), with changes by Calder (1996), Platia (2007Platia ( , 2012, and Girard (2017); Pseudomelanactini sensu Johnson (2002a); Pyrophorini sensu Costa (1975), plus Metapyrophorus Campyloxeninae sensu Costa (1975), plus Malalcahuello Arias-Bohart, 2015; Hemiopinae sensu Lawrence et al (1999), with an additional genus transferred there by Douglas (2011); Lissominae sensu Lawrence and Arias (2009) and Arias-Bohart (2013), but excluding Oestodinae (see Kundrata et al 2016); Oestodinae sensu…”
Section: Methodsmentioning
confidence: 99%
“…Various suprageneric classifications have been proposed for the family, and also generic limits often considerably vary between different authors (e.g., Fleutiaux 1947a;Hayek 1973;Gurjeva 1974a, b;Dolin 1975;Stibick 1979;Calder 1996;Sánchez-Ruiz 1996;Cate et al 2007;Costa et al 2010;Kundrata et al 2018a). Although recent catalogues are available for some world regions (e.g., Golbach 1994, Calder 1996, Cate et al 2007, Arias-Bohart and Elgueta 2012, Zapata and Sánchez-Ruiz 2012, Aguirre-Tapiero and Johnson 2014, Johnson and Chaboo 2015, Platia and Ghahari 2016, Girard 2017, Tarnawski et al 2018 or for certain suprageneric groups (e.g., Schimmel 1999Schimmel , 2003Schimmel , 2004Schimmel , 2005Tarnawski 1996Tarnawski , 2001Schimmel et al , 2016Schimmel and Tarnawski 2009, 2012Douglas 2017; Kubaczkova and Kundrata 2017;Kundrata et al 2018b, c), a comprehensive catalogue of the world Elateridae fauna is not available. Therefore, many recent studies on Elateridae still follow works by Candèze (1857Candèze ( , 1859Candèze ( , 1860Candèze ( , 1863Candèze ( , 1891, Schwarz (1906a…”
Section: Introductionmentioning
confidence: 99%